Normalizing Glutamine Concentration Causes Mitochondrial Uncoupling in an In Vitro Model of Human Skeletal Muscle. (29th November 2013) - Krajcova, Adela; Ziak, Jakub; Jiroutkova, Katerina; Patkova, Jana; Elkalaf, Moustafa; Dzupa, Valer; Trnka, Jan; Duska, Frantisek
Abstract : Background : Glutamine has been considered essential for rapidly dividing cells, but its effect on mitochondrial function is unknown. Materials and Methods : Human myoblasts were isolated from skeletal muscle biopsy samples (n = 9) and exposed for 20 days to 6 different glutamine concentrations (0, 100, 200, 300, 500, and 5000 µM). Cells were trypsinized and manually counted every 5 days. Seven days before the end of exposure, half of these cells were allowed to differentiate to myotubes. Afterward, energy metabolism in both myotubes and myoblasts was assessed by extracellular flux analysis (Seahorse Biosciences, Billerica, MA). The protocol for myoblasts was optimized in preliminary experiments. To account for different mitochondrial density or cell count, data were normalized to citrate synthase activity. Results : Fastest myoblast proliferation was observed at 300 µM glutamine, with a significant reduction at 0 and 100 µM. Glutamine did not influence basal oxygen consumption, anaerobic glycolysis or respiratory chain capacity. Glutamine significantly ( P = .015) influenced the leak through the inner mitochondrial membrane. Efficiency of respiratory chain was highest at 200–300 µM glutamine ( 90% of oxygen used for adenosine triphosphate synthesis). Increased glutamine concentration to 500 or 5000 µM caused mitochondrial uncoupling in myoblasts and myotubes, decreasing the efficiency of the respiratory chain to 70%. Conclusion : Glutamine concentrations, consistent with moderate clinical hypoglutaminemia (300 µM), bring about an optimal condition of myoblast proliferation and for efficiency of aerobic phosphorylation in an in vitro model of human skeletal muscle. These data support the hypothesis of hypoglutaminemia as an adaptive phenomenon in conditions leading to bioenergetic failure (eg, critical illness).